In what ways does pupil consultation improve teaching and learning within a Humanities department? - Burch, M (2021)
The research investigates the opportunities that can arise for the improvement of teaching and learning through the use of student consultation. The key theme that emerges from the literature is that if it is implemented correctly, student consultation can bring many benefits to both teachers and students. This small-scale evaluation project was designed to understand if benefits could be seen through a pilot study in the Humanities department of my school over the course of an 8-week period. The research project was hampered by the impacts of COVID-19 and so only parts of the data collection could take place. Analysis was undertaken and links can be seen between the literature and the data collected with key themes emerging that often agreed with previous research. Students had constructive pieces of advice for the improvement of teaching strategies, prep setting strategies and marking and feedback, which suggests that if a complete research cycle was undertaken, positive strides could be made towards the improvement of teaching and learning.